Comparison of two neonatal pain assessment tools (Children and Infant's Postoperative Pain Scale and the Neonatal Facial Coding System—Revised) and their relations to clinicians' intuitive pain estimates. (12th December 2018) - Kappesser, Judith; de Laffolie, Jan; Faas, Dirk; Ehrhardt, Harald; Hermann, Christiane
Abstract: Background: Many neonatal observational pain assessment tools are available. Their application in clinical settings, however, has been limited. A further difficulty for decision makers may be to choose among the variety of available tools the appropriate one(s) for their patients. Aims of the present study were (1) to compare two commonly cited neonatal pain assessment tools, the Neonatal Facial Coding System—Revised (NFCS‐R) and the Children and Infant's Postoperative Pain Scale (CHIPPS), with regard to their psychometric qualities and (2) to explore intuitive clinicians' ratings by relating them to the tools' items. Methods: Three coders applied both pain assessment tools to videos of 44 neonates who were videotaped while undergoing a painful and a stressful procedure. Clinicians rated the pain neonates experienced on a numerical rating scale. Analyses of variances and regression analyses were used to investigate whether tools could discriminate between the procedures and whether tools' items were predictors of intuitive clinicians' ratings. Results: Interrater reliability, internal consistency and relative convergent validity were high for both assessment tools. Both tools discriminated between painful and stressful situations equally well. Roughly one third of variance in clinicians' intuitive ratings could be explained by items of each tool, however, no single item was found to be a significant predictor. Conclusions: Both pain assessment tools performed equally well regarding psychometric comparisons. Therefore, clinical utility needs to be considered when having to choose. Possibilities of improvement for both tools were identified. Cues clinicians base their intuitive pain judgements need to be further investigated. Significance: Psychometric comparisons of neonatal assessment tools provide useful information that can help health care professionals to choose among tools and researchers to improve them. Both tools compared here performed psychometrically equally well. Their clinical utility, however, can be improved, for example by providing a manual (CHIPPS) and training opportunities.